(untitled) (Vallis Aurea, 2019)
The matter of role and influence of the United Nations in resolution of international conflicts is decisive because they demonstrate their legal presence at the national as well as international level. Throughout the paper, the authors insist on determination of resolution of international conflicts pursuant to Chapter VII of the Charter of the United Nations. The basic hypothesis of the paper has been established on the premise by studying relevant provisions of 1945 Charter of the United Nations, 1949 Geneva Conventions and two additional protocols of 1977, United Nations resolutions, international treaties and international customary rules of war, it is possible to accurately determine the role, character and significance of the United Nations Security Council and the United Nations General Assembly in resolution of international conflicts. Furthermore, it is of interest to note that decisive significance for confirmation of the hypothesis lies with the objective image of the United Nations presented through mechanisms of the international law for resolution of armed conflicts. Furthermore, throughout the entire paper, the authors present international conflict resolution instruments as well as applicable legal consequences of effective resolution of the same, and ultimately, in the concluding considerations, they confirm that actions regarding resolution of armed conflicts are current, essential and timely.